A Transient Driver for Fast Opening of Diaphragmless Shock Tube - Shijie BAI; Shilong LI; Yecheng SONG; Xingyu LIANG; Kun WANG (气体物理, 2025)
Diaphragmless shock tubes, which circumvent diaphragm rupture, effectively mitigate interference from diaphragm fragments in the test section, thereby significantly enhancing testing frequency and result reproducibility. However, the prolonged opening time remains a major constraint on the widespread adoption of this shock tube variant. In this study, leveraging the principles of deformable control volume theory, mass stratification, and empirical formulas for supercritical discharge through throttle orifices, a novel piston-driven diaphragmless propulsion device was designed. The influence of key parameters such as mass distribution/material selection and orifice ratio on the opening time was analyzed and compared. Additionally, comprehensive static and dynamic analyses were conducted to evaluate the structural load capacity and stress distribution of the overall design. The findings reveal that utilizing polyether ether ketone (PEEK) for the main piston fabrication reduces the opening time of the novel diaphragmless device to 1.4 ms, representing an improvement over traditional shock tubes with aluminum diaphragm rupture (approximately 1.56 ms).